Characterization of software-defined radio implementation of a vector network analysis system - Ambatali, Charleston Dale M.; Marciano, Joel Joseph S. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Software Defined Radios (SDR) are radios that are composed of RF front end and digital backend which is separated by a high speed analog to digital converter. The RF front end is capable of operating in a large range of frequencies and its bandwidth is tunable. The digital backend is composed of a digital signal processor and an operating system for user interface which enables the platform to be programmed by a user for a specific application. This reconfigurability enables the same platform to shift to different communication standards. With its digital processing backend and reconfigurable front end, an SDR is a suitable test and measurement instrument in the field of RF Engineering and Wireless Communications. Measurements in RF Engineering and Wireless Communications can be classified into three categories: signal analysis, spectrum analysis, and network analysis. Signal analysis and spectrum analysis requires minimal hardware and some signal processing power to implement a Fast Fourier Transform (FFT), which are already implemented in common SDRs. On the other hand, network analysis is not straightforward since it requires a number of RF front-end resources which adds errors to the measurement and post-processing is needed to de-embed these errors in the measurement. An example of an instrument which measures network parameters is the vector network analyzer (VNA). The common architecture used for VNAs require a single transmitter, three receivers, two couplers, one power splitter, and a digitally-controlled switch. Post-processing include the ability of the software to add and multiply matrices of complex numbers which is possible on an SDR. In terms of hardware, however, there is a challenge in implementing network analysis as SDRs in the market does not necessarily have enough transmit and receive ports to function as a VNA. To address this problem, a novel architecture is proposed to make efficient use of a common 2x2 Multiple Input Multiple Output (MIMO) SDR front-end resources with a corresponding calibration algorithm. It is shown through simulation that the proposed architecture and calibration algorithm is feasible in deem bedding the errors present in the setup. Comparing it with a commercial VNA, the error floor of the SDR-VNA is significantly higher and this can be attributed to the non-idealities in the architecture.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Software radio